Menthol cigarette pricing at military and community retail outlets in the United States - Poston Walker SC; Jahnke Sara A; Haddock Christopher K; Hyder Melissa L; Taylor Jennifer E; Lando Harry A; Kaipust Christopher M (BMC, 2012)
Abstract Background Cigarette prices at military exchanges historically have been discounted. DoD Instruction 1330.9 has mandated that prices be within 5% of the price offered in the local community since 2001. Because minorities are highly represented in the military, we determined whether menthol cigarette prices, the leading choice of African Americans, were compliant with the instruction. Methods We collected, via telephone, menthol cigarette price data from 48 randomly selected US military installation exchanges and matched local area Walmarts. We collected prices after taxes to determine the cost to consumer. Newport was selected as the index brand for menthol cigarettes because it is the leading and second leading brand smoked by African Americans and by Hispanics, respectively and has the second overall highest market share in the US. Results Smokers purchasing menthols at exchanges would realize average savings of 22.78%. There were no significant differences in savings based on military service (F = 1.850, p = 0.152) or US Census Division (F = 1.226, p = 0.311: data not shown). In addition, not a single exchange price was compliant with the DoD instruction. Conclusions Newport menthol cigarettes at military exchanges cost substantially less than the nearest Walmart, with an average savings of 23%. Our findings demonstrate that menthol cigarettes are substantially discounted on military installations, in a manner similar to other cigarette prices, and that DoD Instruction 1330.09 is not enforced.